The Social Life of Biometrics - Grinnell, George C. (Book collections on Project MUSE., 2020)
"In The Social Life of Biometrics, biometrics is loosely defined as a discrete technology of identification that associates physical features with a legal identity. Author George Grinnell considers the social and cultural life of biometrics by examining what it is asked to do, imagined to do, and its intended and unintended effects. As a human-focused account of technology, the book contends that biometrics needs to be understood as a mode of thought that informs how we live and understand one another; it is not simply a neutral technology of identification. Placing our biometric present in historical and cultural perspective, The Social Life of Biometrics examines a range of human experiences of biometrics. It features individual stories from locations as diverse as Turkey, Canada, Qatar, Six Nations territory in New York State, Iraq, the skies above New York City, a university campus and Nairobi to give cultural accounts of identification and look at the ongoing legacies of our biometric ambitions. It ends by considering the ethics surrounding biometrics and human identity, migration, movement, strangers, borders, and the nature of the body and its coherence. How has biometric thought structured ideas about borders, race, covered faces, migration, territory, citizenship, and international responsibility? What might happen if identity was less defined by the question of "who's there?" and much more by the question "how do you live?""--